Differences in creativity across Art and STEM students: We are more alike than unalike. (December 2020) - van Broekhoven, Kim; Cropley, David; Seegers, Philipp
Highlights: This research sheds additional light on long-standing debates regarding domain-generality/specificity and creativity. We examined differences in creativity within and between: (a) General Thematic Areas (Art and Science); (b) Specific Science domains (STEM), and; (c) Engineering micro-domains, for a total of 2277 undergraduate students in German tertiary institutions. Openness, Creative Self-Efficacy and Divergent Thinking are domain-general pre-requisites for creativity, while individuals' assessment of product creativity, and the relative importance of originality, feasibility and effectiveness to creativity, are domain-specific. Educational support for creativity should foster openness, CSE and divergent thinking as broadly as possible, from Kindergarten through to University education. In contrast, the perception of creativity in products is shaped by the needs, standards and cultures of the disciplines that produce those creative outcomes. Abstract: The aim of the present research is to investigate creativity differences, and the magnitude and nature of those differences, among university students. More specifically, we examined differences in creativity within and between: (a) General Thematic Areas (Art and Science); (b) Specific Science domains (STEM), and; (c) Engineering micro-domains, for a total of 2277 students in German tertiary institutions. The results showed many statistically significant, but uniformly small, differences at all levels, across a range of Person, Process and Product variables. The pattern of results suggests that Openness, Creative Self-Efficacy and Divergent Thinking may be general pre-requisites for creativity. In contrast, the way that characteristics of creative products (e.g. originality) are perceived appears more complex. This research sheds additional light on long-standing debates regarding domain-generality/specificity and creativity.